Kylie Christmas [compact disc] - Minogue, Kylie; Sinatra, Frank, 1915-1998; Pop, Iggy, 1947-; Corden, James (Warner Bros./Parlophone, 2015)
Global pop superstar Kylie Minogue rings in the season with her first ever Christmas album, which sees her put her own spin on a mix of holiday classics and originals. There are also duets with Iggy Pop and James Corden.